PENGARUH EMBARGO MINYAK MENTAH IRAN OLEH UNI EROPA TERHADAP PEREKONOMIAN IRAN (2012-2014) - Ermayanti, Diah; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This article analyze the economic impact of EU embargo for Iran’s Crude Oil by various thingkers of Charles Kindleberger and others about this issue. This articles begins the Iran’s Nuclear as a threat to west countries especially for US and EU. Which is they hardly against this programme. Nuclear weapons in the hands of the Iranian regime will have severe repercussion for American security and the security of their allies. The desicion was taking by United Nation to push Iran down and stop the Nuclear programme. Exactly this desicion had impact for any aspect, including economic.Keywords : embargo, Nuclear, economic, hegemony